Penemuan makna hidup dalam Novel Seporsi Mie Ayam Sebelum Mati: Analisis Logoterapi Viktor Frankl - Fawwaz, Ibnatia Hasna (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the existential suffering and search for meaning in life experienced by the main character Ale in Bhrian Khrisna's novel Seporsi Mie Ayam Sebelum Mati (A Bowl of Chicken Noodles Before Death). This novel was chosen because it presents existential issues about the Existential Vacuum, which are rarely discussed in depth in Indonesian popular literature, particularly how the decision to end one's life can develop into a spiritual and social journey that determines the direction of a character's life through the interpretation of suffering. The focus of this study lies on two aspects, namely the form of existential suffering experienced by the character and the process of discovering the meaning of life. The research method used is descriptive qualitative with a literary psychology approach. The analysis is carried out through intensive reading and interpretation of the novel text by highlighting quotations that reflect inner conflict, moral dilemmas, and existential dimensions. Viktor Frankl's Logotherapy theory is used to understand the process of searching for meaning in life through responsibility, accepted suffering, and contribution to others. The results of the study show that the main character experiences existential suffering characterized by self-hatred and loss of purpose in life. The main finding shows that the character succeeds in finding meaning in life through Radical Acceptance of reality and authentic contribution to others, which leads to inner freedom and true peace.